Process for genetically engineering acidophilic bacteria and constructing a transformation vector - Christ, Ana Paula Guarnieri; Alexandrino, Fabiana; Garcia, Oswaldo Jr. (Instituto Nacional de Propriedade Industrial (INPI), 2012)
The present invention describes a method for transforming chemolithotrophic acidophilic bacteria using electroporation technology. The proposed method allows transforming a bacterial line using a transformation vector, the pAF vector, which contains an origin of vegetative replication that allows the vector to replicate inside the bacteria without altering the natural physiological functions of the latter. Also disclosed is the use of the bacteria modified according to the invention in bioleaching processes of sulphated copper, gold, uranium, nickel, zinc and cobalt ore, inter alia.
Processo: CA2832932A1
Número de publicação: CA2832932 (A1)
Número de aplicação: CA20122832932